KINETICS AND MECHANISM OF SORPTION OF COPPER (II) IONS BY ION EXCHANGER - Nazirov Zulqaynar Sharofovich,; Turabdzhanov Sadritdin Maxamatdinovich,; Kedelbayev Bakhitjan Shilmirzaevich,; Drabkova Tatyana Vladimirovna,; Eshimbetov Alisher Gulumbaevich,; Rakhimova Latofat Sobirjonovna, (Academic Scientific Journal of Chemistry, 2020)
In this article the kinetics of the process of sorption of copper (II) ions from aqueous solutions by polymer sulfonic cation exchanger, an elementary unit containing a heterocycle and a sulfonic group, under static conditions at a temperature of 298 K and a copper concentration of 2 mmol / mg is investigated. The sulfonic cation exchanger was preliminarily obtained by the reaction of polycondensation of diphenyl oxide and furfural with further sulfonation to obtain functional ionogenic groups in order to increase the extraction efficiency. The obtained kinetic curves of the dependence of the degree of extraction of copper ions from solution on time were processed using the Boyd, Adamson, and Myers equation, which describes diffusion in a limited volume of solution. The kinetic parameters of the sorption process (effective diffusion coefficient, etc.) are calculated, and the results obtained are compared with the data for the traditionally used industrial cation exchanger, which is a copolymer of styrene and divinyl benzene. It has been established that the process of sorption of copper (II) ions in the sulfonic cation exchanger phase is of an intra diffusion nature and corresponds to second-order kinetic equations.